Aspergillus Thyroiditis: An Incidental Diagnosis in a Patient of Tubercular Meningitis, A Case Report - Sinha, Bipasha; Sutradhar, Arpita; Bhaumik, Sanjay (Annals of Pathology and Laboratory Medicine, 2024)
Fungal thyroiditis is a rare disorder of the thyroid gland and affects immunocompromised patients in a setting of disseminated disease and contributes to high mortality rates. The commonest fungus implicated is Aspergillus. Here, we present a case of Aspergillus Thyroiditis in a patient undergoing treatment for Chronic meningitis (? Tubercular) who was incidentally detected with the thyroid lesion on follow-up evaluation by 18 Fluorodeoxyglucose Positron Emission Tomography (FDG PET). A Fine Needle Aspiration cytology revealed Fungal hyphae and she was diagnosed with Aspergillus thyroiditis. She also had concurrent aspergillosis of the lung. She was treated with antifungals and is doing well at present.